Distinct contribution of axonal and somatodendritic serotonin transporters in drosophila olfaction. (15th December 2019) - Kasture, Ameya Sanjay; Bartel, Daniela; Steinkellner, Thomas; Sucic, Sonja; Hummel, Thomas; Freissmuth, Michael
Abstract: The serotonin transporter (SERT) regulates serotonergic neurotransmission by retrieving released serotonin and replenishing vesicular stores. SERT is not only delivered to axons but it is also present on the neuronal soma and on dendrites. It has not been possible to restrict the distribution of SERT without affecting transporter function. Hence, the physiological role of somatodendritic SERT remains enigmatic. The SERT C-terminus harbors a conserved RI-motif, which recruits SEC24C, a cargo receptor in the coatomer protein-II coat. Failure to engage SEC24C precludes axonal enrichment of SERT. Here we introduced a point mutation into the RI-motif of human SERT causing confinement of the resulting - otherwise fully functional - hSERT-R 607 A on the somatodendritic membrane of primary rat dorsal raphe neurons. Transgenic expression of the corresponding Drosophila mutant dSERT-R 599 A led to its enrichment in the somatodendritic compartment of serotonergic neurons in the fly brain. We explored the possible physiological role of somatodendritic SERT by comparing flies harboring wild type SERT and dSERT-R 599 A in a behavioral paradigm for serotonin-modulated odor perception. When globally re-expressed in serotonergic neurons, wild type SERT but not dSERT-R599A restored ethanol preference. In contrast, dSERT-R599A restored ethanol preference after targeted expression in contralaterally projecting, serotonin-immunoreactive deuterocerebral (CSD) interneurons, while expression of wild type SERT caused ethanol aversion. We conclude that, in CSD neurons, (i) somatodendritic SERT supports ethanol attraction, (ii) axonal SERT specifies ethanol aversion, (iii) the effect of axonal SERT can override that of somatodendritic SERT. These observations demonstrate a distinct biological role of somatodendritic and axonal serotonin transport. This article is part of the issue entitled 'Special Issue on Neurotransmitter Transporters'. Graphical abstract: Image 1 Highlights: HSERT-R607A mutant can be used to study the contribution of somatodendritic SERT. In fruit flies somatodendritic and axonal SERT supported distinct odor responses. The insights have implications for the antidepressant action of SERT inhibitors.